2020
DOI: 10.3390/sym12030390
|View full text |Cite
|
Sign up to set email alerts
|

On (p,q)-Sumudu and (p,q)-Laplace Transforms of the Basic Analogue of Aleph-Function

Abstract: In this paper, we introduce the definitions of Sumudu and Laplace transforms of first and second kind in quantum calculus by using functions of several variables. On account of the general nature of the ( p , q ) -analogue of Aleph-function, a large number of new and known results for these transforms were obtained. Also, we obtain some interesting relationships and identities for these transforms. We also derive some correlations among Aleph function and the above-mentioned integral transforms in quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Laplace transform [40,[45][46][47] Definition of quantum Laplace transform and its properties [38][39][40][41][42][43][44][45][46][47][48] Using the Laplace transform to solve engineering problems 48 Report an incorrect use of the Laplace transform to solve a specific type of the Schrödinger equation Englefield (1968) used the Laplace transform method to examine the problem of the one-dimensional quantum harmonic oscillator [37]. Further, it has been shown that the wave function which defines a quantum mechanical system can be represented by the Laplace transform of a certain distribution and the result of a certain subclass [38].…”
Section: Mathematical Tool References Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Laplace transform [40,[45][46][47] Definition of quantum Laplace transform and its properties [38][39][40][41][42][43][44][45][46][47][48] Using the Laplace transform to solve engineering problems 48 Report an incorrect use of the Laplace transform to solve a specific type of the Schrödinger equation Englefield (1968) used the Laplace transform method to examine the problem of the one-dimensional quantum harmonic oscillator [37]. Further, it has been shown that the wave function which defines a quantum mechanical system can be represented by the Laplace transform of a certain distribution and the result of a certain subclass [38].…”
Section: Mathematical Tool References Objectivementioning
confidence: 99%
“…Then, using q-integral definition on quantum analogs, Alp & Sarikaya (2023) described the đť‘ž Ě…-Laplace transform and some of its properties along with formulas of q-Laplace transform and applications [46]. Sumudu and Laplace transforms of the first and second kind have been defined in quantum calculus for functions of several variables, and some interesting relationships and identities for these transforms are described [47]. Correlations among Aleph functions and the above-mentioned integral transforms in quantum calculus have been derived.…”
Section: Mathematical Tool References Objectivementioning
confidence: 99%
“…In 2019, Sadjang [42] studied the (p, q)-analogues of the Sumudu transform and gave some properties to solve (p, q)-difference equations. In 2020, Tassaddiq et al [47] proposed (p, q)-analogues of Laplace and (p, q)-analogues of Sumudu transforms with (p, q)-Aleph function. Recently, Jirakulchaiwong et al [31] established (p, q)-analogues of Laplace-type integral transforms and use some obtained properties to apply some (p, q)-differential equations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many works established Laplace integral transforms of special functions like Gauss's and Kummer's functions [29], generalized hypergeometric functions [30,31], Aleph-Functions [32], and Bessel functions [33]. Whereas, some formulas corresponding to integral transforms of orthogonal matrix polynomials are little known and traceless in the literature.…”
Section: Introductionmentioning
confidence: 99%